MACRO MANAGEMENT IN MODERN CONDITIONS - Mandić, Ivan (BizInfo Blace, 2010)
Macro management action in the time of all turbulent changes in the environment, largely imposed by the phenomenon of economic globalization, every day are more evident. We should, at the same time, keep in mind that the possible effects of more or less efficient macro management not exhaust the full-time insight into its implementation. On the contrary, the quality and range of current macro management decisively determines the pace and direction of economic and social development of the country in the future.